Gender and Politeness of Request Expression on Whatsapp - Saritza, Zuhra; Natsir, Muhammad (TRANSFORM: Journal of English Language Teaching and Learning, 2022)
The research discussed about politeness strategy used by male and female students in requesting on WhatsApp message. The aims of this study were: to find out the types of politeness strategy used by male and female students by using Brown and Levinson (1987) politeness theory, to find out the differences and reason of politeness strategy used by male and female students in requesting on WhatsApp. The descriptive qualitative method were used in this research, and the data were derived from the WhatsApp message script. The findings of the study showed that male students applied 3 politeness strategies proposed by Brown and Levinson (1987): bald-on record (21 sentences), positive politeness (8 sentences), negative politeness (3 sentences). The researcher also found that female students applied 4 politeness strategies proposed by Brown and Levinson (1987): bald-on record strategy (5 sentences), positive politeness (7 sentences), negative politeness (17 sentences), and off record (5 sentences). The significant difference in politeness strategies used by male and female students are that there is no off record strategy used by male students, they apply the bald-on record strategy more often, while female students are more varied in using of politeness strategies and mostly applied the negative politeness. The difference of male and female students politeness strategy in requesting on WhatsApp because each gender has own way in conveying their want. Male students were more direct when requesting to others, while female students were more indirect when requesting to others.